Edukasi Perawatan Paliatif Berbasis Komunitas sebagai Upaya Peningkatan Quality of Life Pasien Kronis di Rumah - Helmi Juwita; Nurwahita; Intang, Lulu Nur; Klara, Wanda Apriliani; Rusmini, Rusmini; Hidayat, Rahmat; Anita, Tanri (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aims to improve the knowledge of community health cadres and families in providing palliative care to enhance the quality of life of patients with chronic illnesses at home. The program employed education and training methods, with data collected through pre- and post-test questionnaires on palliative care knowledge. Data were analyzed using the Wilcoxon test. The results show that before the palliative care education, participants’ knowledge levels were categorized as fair (61%; 14 participants), good (30%; 7 participants), and poor (9%; 2 participants). After the education, 96% (22 participants) demonstrated good knowledge, and 4% (1 participant) showed fair knowledge. The Wilcoxon test results indicated a significant increase in knowledge after the palliative care education, with a p-value of 0.01. The increase in knowledge strengthened the role of community health cadres in assisting, monitoring, and providing palliative care for patients with chronic diseases at home.